Les imaginaire(s) du voyage à travers un projet de recherche création en danse - Biliana Vassileva (Carnets)
The study approaches the concept of « travel imaginaries » » as choreographic and performance activity. It addresses the need of contemporary dance artists to travel, blending Eastern and Western dance techniques. The main focus is on an interplay of intercultural knowledge within the development of an academic based research creation project, called Drifting/A la dérive, developed by the author. It combines literature, visual arts and dance movement. The project takes place(s) from 2012 till today, and consists of a coherent series of videos, based on traveling and performance practice in East/West destinations. Its methodology of creative « travel imaginaries » constructions encourages « practice as research » approaches to aesthetics.